Effect of Sales Promotions and their Availability on Consumers’ Buying Behaviour: A Perspective on Personal Hygiene Products - Shah, Paragi Kuntal; Mehta, Bijal Nishant (Indian Journal of Marketing, 2012)
The current market is cluttered with promotions and lucrative marketing offers in any and every category of consumer products. However, consumer loyalty still ranges supreme as a benchmark for comparisons, which acts as a prime barrier to consumer responses to different sales promotion schemes. The present paper attempts to investigate the consumer reflections on various sales promotion schemes in the Indian personal care market in accordance with several other important factors like availability, consistency in schemes, packaging and so on. The impact and influence of such factors are discussed in detail in the paper. The study highlights consumer responses to various marketing tactics used by different companies and analyses purchase decisions made during various sales promotion schemes and after viewing advertisements. It is concluded that sales promotions are considered to be a successful and effective weapon in the hands of the companies to make more sales and influence consumers to purchase personal care products as the consumers are rarely brand loyal for this category of products. However, sales promotion schemes may win a "share of the mind" but do not guarantee a place in the "share of the heart" for the firm.